An annotated list of species of the Proteocephalus Weinland, 1858 aggregate sensu de Chambrier et al. (2004) (Cestoda: Proteocephalidea), parasites of fishes in the Palaearctic Region, their phylogenetic relationships and a key to their identification - Scholz, Tomás; Hanzelová, Vladimíra; Skeríková, Andrea; Shimazu, Takeshi; Rolbiecki, Leszek (Systematic parasitology, 2007)
A list and key to the identification of valid species of tapeworms of the Proteocephalus Weinland, 1858 aggregate sensu de Chambrier et al. (2004), i.e. species of the genus occurring in fresh- and brackish-water fishes in the Palaearctic Region, are provided, with data on their hosts and geographical distribution. Instead of 32 taxa listed by Schmidt (1986) and subsequent authors, only the following 14 species are considered to be valid: P. ambiguus (Dujardin, 1845) (type-species); P. cernuae (Gmelin, 1790); P. filicollis (Rudolphi, 1802); P. fluviatilis Bangham, 1925; P. gobiorum Dogiel & Bychowsky, 1939; P. longicollis (Zeder, 1800); P. macrocephalus (Creplin, 1825); P. midoriensis Shimazu, 1990; P. percae (Müller, 1780); P. plecoglossi Yamaguti, 1934; P. sagittus (Grimm, 1872); P. tetrastomus (Rudolphi, 1810); P. thymalli (Annenkova-Chlopina, 1923); and P. torulosus (Batsch, 1786). An analysis of sequences of the nuclear genes (ITS2 and V4 region of 18S rDNA) revealed the following phylogenetic relationships for these taxa: P. torulosus ((P. midoriensis, P. sagittus) (P. fluviatilis (P. filicollis, P. gobiorum, P. macrocephalus)) (P. cernuae, P. plecoglossi, P. tetrastomus ((P. longicollis, P. percae) (P. ambiguus, P. thymalli)))). P. pronini Rusinek, 2001 from grayling Thymallus arcticus nigrescens is synonymised with P. thymalli. P. esocis La Rue, 1911 is apparently invalid but its conspecificity with either P. percae or P. longicollis could not be confirmed due to the absence of the scolex in the holotype and the unavailability of other material for morphological and molecular studies. P. osculatus (Goeze, 1782) has recently been transferred to Glanitaenia de Chambrier, Mariaux, Vaucher & Zehnder, 2004. The validity of the genus is supported by the position of G. osculata within the Proteocephalidea, based on molecular data, as well as its morphology and nature of the definitive host (the European wels Silurus glanis). P. hemispherous Rahemo & Al-Niaeemi, 2001, described from S. glanis in Iraq, is transferred to Postgangesia Akhmerov, 1960 as Postgangesia hemispherous (Rahemo & Al-Niaeemi, 2001) n. comb.
Keywords: Cestoda; DNA helmintů; DNA, Helminth; sekvence nukleotidů; polymerázová řetězová reakce; fylogeneze; RNA, Ribosomal, 18S; RNA ribozomální 5.8S; Phylogeny; molekulární sekvence - údaje; sekvenční seřazení; mezerníky ribozomální DNA; ryby; Fishes; Animals; zvířata; DNA, Ribosomal Spacer; Molecular Sequence Data; Polymerase Chain Reaction; Base Sequence; RNA ribozomální 18S; RNA, Ribosomal, 5.8S; Sequence Alignment